Change of Circulating Vascular Endothelial Growth Factor Level and Reduction of Anhedonia Are Associated in Patients With Major Depressive Disorder Treated With Repetitive Transcranial Magnetic Stimulation - Elemery, Monika; Kiss, Szilvia; Dome, Peter; Pogany, Laszlo; Faludi, Gabor; Lazary, Judit (Frontiers in Psychiatry, 2022)
Aim: Vascular endothelial growth factor (VEGF) has been implicated in mediating the effect of antidepressant therapies since it plays a significant role in the neurogenesis. Anhedonia, an endophenotype of major deperssion disorder (MDD) is related to the dorsolateral prefrontal cortex, the major focus of brain stimulation in MDD The aim of our study was to analyse the change of serum VEGF level after rTMS treatment in association with anhedonia Methods: A dataset of 17 patients with TRD who were treated with AD and bilateral rTMS for 2x5 days was analysed. Depression was measured by the Montgomery-Asberg Depression Scale (MADRS) and anhedonia by the Snaith-Hamilton Pleasure Scale (SHAPS) for monitoring the symptom changes. The serum VEGF levels and symptoms were assessed on the first (V1), on the 14th (V2) and on the 28th day (V3). The VEGF was measured by ELISA assay. Results: There was no significant association between MADRS score and serum VEGF level at any timepoint. Decrease of the SHAPS score was significantly associated with the increase of VEGF level between V1 and V2 (p=0.001). The VEGF levels were significantly higher in non-responders compared to responders (p=0.04). The baseline VEGF level has been proven as a significant predictive factor of treatment response (p=0.045). Conclusions: Our results suggest that serum VEGF can be sensitive for changes of anhedonia during the rTMS treatment. Measure of anhedonia in rTMS treatment studies of TRD patients can be suggested for development of more appropriate treatment recommandation system in different subtypes of depressive disorders.